Mapping Acid–Base Sites on Anatase Titania (100) and (101) Surfaces by Density Functional Theory: The Link Between Lewis Acidity and the Surface Ability to Flex - Alexey V. Ignatchenko; Paige E. Denman (Surfaces)
The acidity of anatase titania before and after KOH doping was probed by pyridine adsorption in a pulse microreactor and modeled by DFT optimization of the geometry of CO and pyridine adsorption on a periodic slab of (101) and (100) surfaces using a GGA/PBE functional and verified by an example of a single-point calculation of the optimized geometry using an HSE-06 hybrid functional. The anatase (101) surface was slightly more acidic compared to the (100) surface. Both experimental and computational methods show that the acidity of anatase surfaces decreased after KOH doping and increased after the dissociative adsorption of water. Higher acidity of Ti metal centers was indicated by the shortening of the Ti-N, Ti-C, and C-O bond lengths, increasing the IR frequency of CO and pyridine ring vibrations and energy of adsorption. The DFT calculated energy of pyridine adsorption was analyzed in terms of binding energy and the energy of lattice distortion. The latter was used to construct Hammett plots for the adsorption of 4-substituted pyridines with electron-donating and -withdrawing substituents. The Hammett rho constant was obtained and used to characterize the acidity of various metal centers of −1.51 vs. −1.46 on pristine (101) and (100) surfaces, which were lowered to −1.07 and −1.19 values on KOH-doped (101) and (100) surfaces, respectively. The mechanism of lowering surface acidity via KOH doping proceeds through the stabilization of the atomic structure of Lewis acid centers. When an alkaline metal cation binds to several lattice oxygen atoms, the surface structure becomes more rigid. The ability of Ti atoms to move toward the adsorbate is restricted. Consequently, the lattice distortion energy and binding energy are decreased. In contrast, higher flexibility of the outermost layer of Ti atoms as a result of electron density redistribution, for example, in the presence of water on the surface, allows them to move farther outward, make shorter contacts with the adsorbate, and attain higher energies of binding and lattice distortion.